PENGARUH INSEKTISIDA TERHADAP MUSUH ALAMI TELUR PENGGEREK BATANG PADA Scirpophaga incertulas Walker - Nurnina Nonci; Fausiah T Ladja (Agroland: Jurnal Ilmu-ilmu Pertanian, 2006)
This study was conducted between January and May 2005 to explore effects of insecticides on the eggs of rice stem borer Scirpophaga insertulas Walker. This was done at the Lanrang experimental farm station and the laboratory of entomology and plant physiology of ICERI. There were four rice varieties used in he experiment (Gilirang, Cigeulis, Lok Ulo and Cibogo), each of which was observed in a 5 x 5 m observation plot.  Observation was done by collecting egg of rice stem borer on selected plant samples. The collected eggs were placed in test tubes, labeled, and brought to laboratory and the parasitoid found was examined under a light microscope. Results showed that for the four rice varieties tested, it was found three parasitoid species on S. incertulas egg i.e. Trichogramma japonicum Ashm., Telenomus rowani Gah., and Tetratichus schoenobi Ferr. Nevertheless, in one egg mass of S. incertulas, not all species of parasitoid found at the same time, sometimes T. japonicum with T. rowani, T. rowani with T. schoenobi, or T. japonicum with T. schoenobi. There was no direct effect insecticide application to parasitoid population.